Essential Oils from Citrus Peels Promote Calcium Overload-Induced Calcicoptosis in U251 Cells - Yurong Li; Juanjuan Wei; Zimao Ye; Chen Ji; Wenji Li; Li Xu; Zhiqin Zhou (Antioxidants)
Citrus peel essential oils (CPEOs) have demonstrated substantial medicinal potential for glioblastoma treatment because of their extensive antitumor effects, low potential for drug resistance, and ability to cross the human blood–brain barrier. In this study, the chemical compositions of five CPEOs were analyzed via gas chromatography–mass spectrometry (GC-MS). CCK8 assays were used to evaluate the ability of five CPEOs to inhibit U251 human glioblastoma cells, and XLB and RA were selected for further investigation. Through wound healing assays and cell cycle and apoptosis analyses via flow cytometry, it was revealed that these CPEOs inhibited cell migration, arrested the cell cycle at G1/G0, and induced apoptosis with similar levels of inhibition. After CPEOs treatment, the intracellular Ca2+ content and reactive oxygen species levels in U251 cells increased significantly, whereas the mitochondrial membrane potential decreased. Additionally, the antioxidant enzyme system (SOD, POD, CAT, and GR) and the nonenzymatic defense system (GSH) were inhibited, leading to an increase in lipid peroxidation. qRT–PCR indicated the significant upregulation of intracellular calcium ion signaling pathways and the upregulation of mitochondrial apoptosis-related genes. Additionally, the activation of calcicoptosis-related indicators induced by the CPEOs could be reversed by inhibitor treatment, confirming that both of the selected CPEOs inhibit tumors by activating calcicoptosis-related pathways. These findings highlight the immense potential of CPEOs in healthcare and pharmaceutical applications by not only providing a scientific basis for the potential application of CPEOs in the treatment of glioblastoma but also offering new insights for the development of novel antitumor drugs.